2020
DOI: 10.3390/ijms21093074
|View full text |Cite
|
Sign up to set email alerts
|

Functional Lipids in Autoimmune Inflammatory Diseases

Abstract: Lipids are apolar small molecules known not only as components of cell membranes but also, in recent literature, as modulators of different biological functions. Herein, we focused on the bioactive lipids that can influence the immune responses and inflammatory processes regulating vascular hyperreactivity, pain, leukocyte trafficking, and clearance. In the case of excessive pro-inflammatory lipid activity, these lipids also contribute to the transition from acute to chronic inflammation. Based on their bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 145 publications
(181 reference statements)
0
27
0
Order By: Relevance
“…Among those pathways, we detected three fatty acid related pathways, such as Fatty acid biosynthesis, Pantothenate and CoA biosynthesis and Fatty acid metabolism. It has been demonstrated that fatty acids play a role in various of RA processes, such as in ammation and pain, by interacting with immune cells like Th17 cells [29,30]. It has been demonstrated that fatty acid contributed synthesis of Th17 cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…Among those pathways, we detected three fatty acid related pathways, such as Fatty acid biosynthesis, Pantothenate and CoA biosynthesis and Fatty acid metabolism. It has been demonstrated that fatty acids play a role in various of RA processes, such as in ammation and pain, by interacting with immune cells like Th17 cells [29,30]. It has been demonstrated that fatty acid contributed synthesis of Th17 cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid alterations can be observed even before disease manifestations, which suggests that these molecules are closely linked to the most widespread metabolic changes caused by inflammation (associated with TNF-α) [ 138 , 139 ]. As a result, it is important to study in deep the lipid modulation by RA as it can provide potential markers for early diagnosis of this disease.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Several studies have proposed the use of eicosanoid precursors such as omega-3 polyunsaturated fatty acids (PUFAs) as candidates for the treatment of type 1 diabetes, SLE or RA. These molecules have anti-inflammatory properties ( 44 , 45 ). Also modulation of lipoxins, resolvins and protectins with aspirin is used in the treatment of SLE ( 46 ).…”
Section: Targeting Trained Immunity In Inflammatory and Autoimmune DImentioning
confidence: 99%